Nematode isoenzyme studies and cytogenetics - Yong, Hoi Sen; Mak, J.W. (1988)
The current information on isoenzyme studies of nematode parasites was reviewed. The genetic heterogeneity as reviewed by these studies was highlighted. Application of isoenzyme studies and the role of biotechnological techniques in isoenzyme studies was discussed, and the status of cytogenetic studies on nematode parasites was presented.